2020
DOI: 10.1016/j.molp.2020.01.014
|View full text |Cite
|
Sign up to set email alerts
|

A Domestication-Associated Gene GmPRR3b Regulates the Circadian Clock and Flowering Time in Soybean

Abstract: Improved soybean cultivars have been adapted to grow at a wide range of latitudes, enabling expansion of cultivation worldwide. However, the genetic basis of this broad adaptation is still not clear. Here, we report the identification of GmPRR3b as a major flowering time regulatory gene that has been selected during domestication and genetic improvement for geographic expansion. Through a genome-wide association study of a diverse soybean landrace panel consisting of 279 accessions, we identified 16 candidate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
105
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(108 citation statements)
references
References 63 publications
3
105
0
Order By: Relevance
“…Recent study suggested two homologous PRR3 genes controlling flowering and maturity were sequentially selected during soybean domestication (Lu et al 2020). Another research group also reported that GmPRR3b H6 may have a pleiotropic role favorited for domestication and genetic improvement (Li et al 2020). In our results, SiPRR37 has been shown to contribute to local adaptation of foxtail millet.…”
Section: Siprr37 Contributed To the Local Adaptation To The Northeastsupporting
confidence: 69%
“…Recent study suggested two homologous PRR3 genes controlling flowering and maturity were sequentially selected during soybean domestication (Lu et al 2020). Another research group also reported that GmPRR3b H6 may have a pleiotropic role favorited for domestication and genetic improvement (Li et al 2020). In our results, SiPRR37 has been shown to contribute to local adaptation of foxtail millet.…”
Section: Siprr37 Contributed To the Local Adaptation To The Northeastsupporting
confidence: 69%
“…LHY proteins bind to the promoter of E1 to suppress its transcription, and in turn release its transcriptional suppression of the two key soybean FT homologs, ultimately resulting in promotion of flowering and earlier maturity (Figure 1). The Tof12 locus and its causative gene PRR3b were also characterized in other recent studies, highlighting the functional significance of this locus in soybean flowering and adaptation (Li et al 2019a(Li et al , 2019bLi et al 2020;Wang et al 2020).…”
mentioning
confidence: 68%
“…LHY proteins bind to the promoter of E1 to suppress its transcription, and in turn release its transcriptional suppression of the two key soybean FT homologs, ultimately resulting in promotion of flowering and earlier maturity (Figure 1). The Tof12 locus and its causative gene PRR3b were also characterized in other recent studies, highlighting the functional significance of this locus in soybean flowering and adaptation (Li et al 2019a, 2019b; Li et al 2020; Wang et al 2020).…”
Section: Figurementioning
confidence: 71%